Creating Pathways for the Poorest : Early Lessons on Implementing the Graduation Model - El-Zoghbi, Mayada; Montesquiou, Aude de; Hashemi, Syed (World Bank, Washington, DC, 2012)
People at the very bottom of the economic ladder are often excluded, or exclude themselves, from microfinance. Their income is usually too low and unreliable to permit repayment of loans or investment in anything but basic food consumption. In some countries the very poor are served by safety net programs, which usually take the form of cash transfers, food aid, or guaranteed employment schemes. Starting in 2006, Consultative Group to Assist the Poorest (CGAP) and the Ford Foundation have been exploring how a 'graduation model' can create pathways out of extreme poverty, adapting a methodology developed by BRAC in Bangladesh. This brief discusses early lessons from the implementation of the graduation model.